PREVENTIVE MEASURES FOR IRON DEFICIENCY ANEMIA AMONG ADOLESCENTS - Yorqin Sattorov; Ogabek Zoirov (Web of Journals Publishing, 2025)
This article is aimed at analyzing the causes of the spread of iron deficiency anemia among adolescents, reviewing international experiences in preventing this condition, and proposing effective preventive measures that can be applied in the context of Uzbekistan. The article is intended to provide practical recommendations not only for healthcare professionals but also for teachers, parents, and representatives of government agencies.
Keywords: Iron deficiency anemia, adolescents, prevention, nutrition, iron fortification, pharmacological prevention, education, screening, Uzbekistan.